2008
DOI: 10.1590/s1516-35982008000700002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tamanho da presa e do acréscimo de ração na larvicultura de pacamã

Abstract: RESUMO -Objetivou-se estudar o efeito do tamanho da presa, com ou sem adição de ração na larvicultura do pacamã (Lophiosilurus alexandri), espécie nativa da bacia do Rio São Francisco ameaçada de extinção. As larvas foram cultivadas em aquários por 16 dias e alimentadas com zooplâncton natural, selecionado em malhas de 650 e 1.300 μm, com ou sem ração.A oferta de zooplâncton de maior tamanho resultou em melhor desenvolvimento das larvas de pacamã, comprovando a vantagem do fornecimento de partículas alimentare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
5
14
0
7
Order By: Relevance
“…Water quality parameters (Table 2) were similar to those observed by other authors for the culture of larvae of pacamã (Pedreira et al, 2008a;Pedreira et al, 2009) and curimatá-pioa , and were similar between treatments, not interfering with the observed differences. The luminosity (L*) differed between tanks with different colors, which influenced the development and survival of pacamã and curimatá-pioa larvae alike.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Water quality parameters (Table 2) were similar to those observed by other authors for the culture of larvae of pacamã (Pedreira et al, 2008a;Pedreira et al, 2009) and curimatá-pioa , and were similar between treatments, not interfering with the observed differences. The luminosity (L*) differed between tanks with different colors, which influenced the development and survival of pacamã and curimatá-pioa larvae alike.…”
Section: Resultssupporting
confidence: 85%
“…Larvae of pacamã ate the same amount of prey when subjected to aquaria of different colors and showed differences in growth between those cultivated in green and black tanks. Pedreira et al (2008a) observed differences in the survival rate and growth of pacamã fed the same number of prey. Luz & Zaniboni-Filho (2001), while subjecting fish larvae to different concentrations of food plankton, did not find a significant difference in survival and growth of larvae.…”
Section: Resultsmentioning
confidence: 79%
“…Some researches focusing on the juvenile production using Artemia nauplii has been done with success for this species (LUZ and SANTOS, 2008;PEDREIRA et al, 2008PEDREIRA et al, , 2009SANTOS and LUZ, 2009;LUZ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They are likely ready to search and capture for prey, which is corroborated by the much faster yolk sac consumption after 11 mm TL. Moreover, experimental exogenous feeding initiates at this length (Pedreira et al, 2008). The period between the IP of mouth length and the end of the yolk sac could be linked to the development and improvement of suction and prey capture before relying fully on exogenous energy for survival (Hunt von Herbing et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ecomorphological and culture experiments have been conducted envisaging the establishment of pacamã larval culture protocols (López & Sampaio, 2000;Pedreira et al, 2008;Guimarães-Cruz et al, 2009;Pedreira et al, 2009;Luz et al, 2011). Recently, Santos et al (2013) published a valuable set of data on reproductive parameter of hormonally induced spawning pacamãs obtained in hatchery conditions.…”
Section: Introductionmentioning
confidence: 99%